Mechanical and degradation behavior of three Fe-Mn-C alloys for potential biomedical applications. (June 2021) - Gambaro, S.; Paternoster, C.; Occhionero, B.; Fiocchi, J.; Biffi, C.A.; Tuissi, A.; Mantovani, D.
Graphical abstract: Highlights: Three Fe-Mn-C alloys with 12, 16 and 20 wt% of Mn were cast, hot rolled and characterized. Fe-12Mn-1.2C showed the highest mechanical properties with E = 157 ± 4 GPa, YS = 490 ± 30 MPa. Fe-20Mn-0.6C formed a MnCO3 crystallized layer under static degradation test in Hanks' solution. Corrosion rate (in vitro) for the alloys was approximately 0.15 ± 0.05 mm/year. Abstract: Three new Fe-Mn-C alloys were cast, hot rolled and characterized as candidate materials for the fabrication of bioresorbable implants. In particular, the effect of different Mn and C contents on phases formation, mechanical properties as well as corrosion rate and degradation pattern in modified Hanks' solution were investigated. A combination of complementary characterization techniques, including SEM-EDS, XRD, FTIR, MP-AES and XPS, was used to identify the degradation products and patterns. These latter were studied both in those attached to sample surfaces and in those collected from the waste solution. The alloy with lower Mn (12 wt%) and higher C (1.2 wt%) content showed only the austenitic phase, while 4 and 25 % of the martensitic phase were detected in alloys with higher Mn content, 16 and 20 wt%, respectively. The increase of Mn content and the corresponding decrease of C caused a continuous drop in the mechanical resistance, while no evident difference in the chemical composition of the degradation products was found for the three alloy compositions. However, the morphology and the chemical composition of the degradation layer on the sample surface were different. After the degradation test, a (Fe, Mn)CO3 cuboid layer formed on all the sample surfaces and it homogeneously extended over the Fe20Mn0.6C samples acting as a compact diffusion and corrosion barrier, responsible for the differences in sample corrosion rates.